New insights of low-temperature plasma effects on germination of three genotypes of Arabidopsis thaliana seeds under osmotic and saline stresses - Bafoil, Maxime (Sci Rep, 2019)
In order to investigate the effects of low temperature plasmas on germination of Arabidopsis thaliana seeds, a dielectric barrier discharge device generating the plasma in ambient air was used. To highlight the different plasma effects on the seed surface, saline and osmotic stresses were considered in the case of reference Col-0 seeds and two further seed coat mutants gl2 and gpat5 to better analyse the seed surface changes and their consequences on germination. The GL2 gene encode a transcription factor controlling the balance between the biosynthesis of fatty acids in the embryo and the production of mucilage and flavonoid pigments in the seed coat. The GPAT5 gene encode for an acyltransferase necessary for the accumulation of suberin in the seed coat which is essential for the embryo protection. The testa and endosperm ruptures are identified to note the germination stage. An increasing of germination rate, possibly due to the modification of mantle layers structure, is observed in most of cases, even in presence of saline or osmotic stress, after plasma treatment. Furthermore, we demonstrated that the germination rate of the gl2 mutant seeds is increased by at most 47% after plasma treatment, contrariwise, the germination of gpat5 mutant being initially lower is inhibited by the same plasma treatment. The scanning electron microscopy pictures and confocal microscopy fluorescence both showed changes of the exterior aspects of the seeds after plasma treatment. Considering these results, we assumed that lipid compounds can be found on the surface. To validate this hypothesis, permeability tests were performed, and it was clearly shown that a permeability decrease is induced by the low temperature plasma treatment.